Factors associated with the mortality of patients hospitalized by COVID-19 in a tertiary hospital - Duarte , Carla Rubia; Carvalho , Beatriz Rezende de Brito; Mesquita , Renan William; Alexandrino , Andderson Gustavo Nogueira; Portella , Auricélia Xavier de Oliveira; Fortes , Paulo Cezar Nunes; Jorge, Alex Sandro; Ferreto, Lirane Elize Defante; Wendt, Guilherme Welter (Seven Editora, 2023)
The pandemic of COVID-19 generated a significant impact on health and socioeconomically globally due to lack of treatment, high transmission, and morbidity and mortality.  In this sense, analyzing the epidemiological scenarios of the disease generates means for health management planning, identification of more susceptible groups, and physiopathological understanding. The objective of this study was to identify factors associated with death in patients hospitalized for COVID-19 in a tertiary care hospital. A cross-sectional study was carried out based on secondary data seen at the hospital unit covered by the 8th Health Regional of Paraná (8thRS), in the year 2020. Data related to the socio-demographic, laboratory, and clinical characteristics of patients were collected, and the outcome analyzed was hospital death (yes/no). Pearson's chi-square test or Fisher's exact test was used to analyze the data. (“Predictors of burnout syndrome in intensive care nurses”) As of December 31, 2020, 185 patients with RT-PCR confirmed diagnosis for COVID-19 were recorded, with 113 discharges (61.1%; 95%CI;54.1 - 68.1) and 72 deaths (39%; 95%CI; 31.9 - 48.2). In summary, we identified higher mortality in the male group, longer periods of hospitalization, and comorbidities present: hypertension, obesity, diabetes, and cardiovascular diseases. DOI: https://doi.org/10.56238/emerrelcovid19-045